Tissue culture unit at Faculty of Pharmacy UiTM Puncak Alam conducts cell culture induction workshop for final year research project students / Nur Fathiah Mohd Radzi and - Mohd Radzi, Nur Fathiah; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
The Tissue Culture Unit at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam, recently held a comprehensive Cell Culture Induction Workshop. This workshop was specifically tailored for final year research project students pursuing the Bachelor in Pharmacy program (B.Pharm) as part of their academic requirements. This workshop, held on March 22nd, 2024, aimed to equip students with the essential knowledge and skills required for successful cell culture experiments. The half-day workshop consisted of three comprehensive sessions, each designed to provide participants with a well-rounded understanding of cell culture procedures and laboratory protocols. The event kicked off with an introduction to the Tissue Culture Unit, where eleven participants were introduced to the laboratory policies, management, and online booking system called the internet Laboratory Integrated Site System (iLISS).